Prophage and Plasmid-Mediated Beta-Lactamases in Multidrug-Resistant Extraintestinal Escherichia coli - Raj, Juliet Roshini Mohan; Dinesh, Akshatha; Vittal, Rajeshwari; Rohit, Anusha (Journal of Health and Allied Sciences NU, 2023)
Objectives Antibiotic resistance can arise as a mutation to adapt to stress or be mediated by horizontal gene transfer. This study aimed at identifying the resistance determinants present in the mobile genetic elements of prophages and plasmids within multidrug-resistant (MDR) extraintestinal Escherichia coli.Materials and Methods Thirty-five anonymized MDR E. coli isolates of nonintestinal infections were confirmed for their antimicrobial resistance to six categories of antimicrobials by the disk diffusion test. Genes coding for beta-lactamases and carbapenemases in bacterial genome, plasmid, and prophage fractions were separately determined by polymerase chain reaction. Transducing ability of prophages carrying resistance genes was determined.Results Twenty-six isolates were positive for the gene blaCTX-M, nine for blaTEM, one each for blaKPC and blaVIM, thirteen for blaNDM, and seven for blaOXA. A majority of these isolates carried these determinants in plasmids and prophage fractions. Twenty-one percent of the prophage fractions (4 of 19) were able to successfully transfer resistance to sensitive isolates.Conclusion This study indicates blaCTX-M, blaTEM, and blaNDM genes that are reported most frequently in MDR isolates are more frequent in the plasmid and prophage fractions thus supporting for increased mobility.
Keywords: beta-lactamase; carbapenemases; mobile genetic elements; MDR E. coli